Weighted Statistical Testing based on Active Learning and Formal Verification Techniques for Software Reliability Assessment - Omri, Fouad ben Nasr (The Karlsruhe Series on Software Design and Quality / Ed. by Prof. Dr. Ralf Reussner, 2018)
This work developed an automatic approach for the assessment of software reliability which is both theoretical sound and practical. The developed approach extends and combines theoretical sound approaches in a novel manner to systematically reduce the overhead of reliability assessment.